An Evaluative Study of Early Childhood Care and Education Programme in Punjab - VERMA, SNEH LATA; SAINI, PROMILA (THE PRIMARY TEACHER, 2014)
In the process of planning and formulating policies related to Early Childhood Care and Education (ECCE), one major drawback that one faces is the lack of a well developed body of research in this field. It is only in the last two decades that researchers from various disciplines have become interested in studying the young child’s growth, development and learning process. It has been discussed at various forums that ECCE has not been provided a due place which it deserved; instead it has been relegated to an innovative activity under Sarva Shiksha Abhiyan. Hence, there is a need to evaluate ECCE programme under the provision of SSA. In the present research, descriptive survey method and purposive sampling technique were used by the investigator to collect data from 60 ECCE workers, 60 community members and 30 parents from Gurdaspur district of Punjab. Self constructed interview and observation schedule was used by the investigator to evaluate the ECCE programme. The investigator explored the views of parents, ECCE workers, community members, District Education Officer and Block Development Officer about the implementation of ECCE programme. The results reflect that there is a need to upgrade infrastructural facilities and teaching learning material in ECCE centres. The DEO and BDO received the funds regularly for ECCE under SSA and ECCE programme in their regime is successful whereas ECCE workers stated that funds are not properly utilised and there are problems of health, food and educational facilities and they deal with the problems on their own. The parents and community members are satisfied with the implementation of ECCE programme in their area and stated that funds are properly utilised and adequate arrangements at ECCE centres in terms of infrastructure and other facilities has changed the lives of children in their area.